3D Surface Profile Construction and Flaw Detection in a Composite Structure - Her, S.-C.; Chu, W.-B. (Проблемы прочности, 2019)
The nondestructive method of evaluating material properties and structural integrity is built upon ultrasonic scanning, raw data acquisition and processing, coming from an ultrasonic transducer. Commercial software LabVIEW designed by National Instruments Inc. is aimed at processing ultrasonic images. An ultrasonic C-scan image system was developed. This system is capable of constructing a 3D surface profile and detecting flaws inside the composite structure. The technique for nondestructive inspection and geometry estimation is validated experimentally on an aluminum plate with small holes and composite structure with a delamination defect. Неразрушающий метод оценки свойств материала и целостности структуры основан на ультразвуковом сканировании, сборе и обработке исходных данных, поступающих от ультразвукового датчика. Коммерческое программное обеспечение LabVLEW, разработанное National Instruments Inc., предназначено для обработки ультразвуковых изображений. Создана ультразвуковая система сканирования изображения С-scan. Система обладает функцией построения трехмерного профиля поверхности и выявления дефектов внутри композиционной структуры. Проверку достоверности методики неразрушающего контроля и оценку геометрии выполняли экспериментально на алюминиевой пластине с небольшими отверстиями и композиционной структуре с дефектом расслоения. Неруйнівний метод оцінки властивостей матеріалу і цілісності структури заснований на ультразвуковому скануванні, зборі та обробці вихідних даних, що надходять від ультразвукового датчика. Комерційне програмне забезпечення LabVLEW, розроблене National Instruments Inc., призначене для обробки ультразвукових зображень. Створена ультразвукова система сканування зображення С-scan. Система має функцію побудови тривимірного профілю поверхні і виявлення дефектів всередині композиційної структури. Перевірку достовірності методики неруйнівного контролю та оцінку геометрії виконували експериментально на алюмінієвій пластині з невеликими отворами і композиційній структурі з дефектом розшарування